A New Perspective of Learning Arabic in Lombok as a World Halal Tourism Destination - Handriawan, Dony (ALSINATUNA, 2020)
This article analyzes the importance of re-orientation in achieving the goals of Arabic Teaching and Learning (ATL). The process is adapted to the local context and the needs of the place where the Arabic language is taught. Lombok currently becomes the main halal tourism destination as a consequence of the awards in the tourism sector achieved by Lombok in 2015 and 2016. In 2015 Lombok won two prestigious awards as "World Best Halal Tourism Destination” and “World Best Honeymoon Destination". Again, in 2016 Lombok won three awards as “World's Best Halal Honeymoon Destination, World's Halal Beach Resort, and World's Best Halal Travel Website” in Abu Dhabi. This is a Research and Development (R&D) using the ADDIE model (Analysis, Design, Develop, Implement and Evaluate). The researcher compiles a new module of Arabic teaching materials that is relevant to context emphasizing Lombok as the main halal tourism destination. The results indicate that ATL activities in Lombok need to be reviewed and re-actualized. In addition, the final product of this study such as the formulation of a tourism-based Arabic learning module is quite significant as an additional locality-based learning resource.